2017
DOI: 10.1002/gj.3011
|View full text |Cite
|
Sign up to set email alerts
|

Provenance and tectonic setting of Early Eocene Sohnari Member of Laki Formation from southern Indus Basin of Pakistan

Abstract: The current study is carried out the bulk mineralogical and geochemical investigation of the Early Eocene Sohnari coal‐bearing sedimentary rocks from the southern Indus Basin in Pakistan. The sediments of the Sohnari Member of Laki Formation are composed of shale and sandstone. Their provenance and tectonic setting can well constrain the evolution of the Indus Basin and help solve the controversy regarding the timing of the India–Eurasia collision. X‐ray diffraction results confirm the existence of abundant qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 73 publications
(148 reference statements)
0
5
0
Order By: Relevance
“…The lithology and mineralogy of Sohnari Member have been discussed in detail by Hakro et al (2017). The Chat Member of Laki Formation is about 111 m thick in this section (Figure 3).…”
Section: Sections Descriptionmentioning
confidence: 88%
See 3 more Smart Citations
“…The lithology and mineralogy of Sohnari Member have been discussed in detail by Hakro et al (2017). The Chat Member of Laki Formation is about 111 m thick in this section (Figure 3).…”
Section: Sections Descriptionmentioning
confidence: 88%
“…Integrated age dating and palaeo-bathymetric demarcations reveal significant basin uplift and erosion at the end of the Cretaceous and end of Eocene times, the latter coinciding with the closure of the Neo-Tethys (Wakefield & Monteil, 2002). However, in a recent study in the Lower Indus Basin, Hakro et al (2017) suggested that the Indian-Asian collision had not occurred at the SW margin during Early Eocene time. The different ideas are due to the different episodes of collision at various geographic positions.…”
Section: Geological Settingmentioning
confidence: 94%
See 2 more Smart Citations
“…The Sohnari member of the Laki Formation (K 2 O) concentration ranges from 0.51% to 0.80%, with a mean value of 0.51% and 0.21%. As compared to other cations (calcium and magnesium), the lattices of montmorillonite often contain small amounts of potassium and sodium oxides [20], and [28]…”
Section: Potassium (K 2 O)mentioning
confidence: 99%